Arteriovenous malformation-related headache and seizures in pregnancy masquerading as eclampsia: A case report - Siou-Ting Lee; Yi-Liang Lee; Ya-Che Chen; Wei Lin; Ching-I Wu; Chi-Kang Lin (Elsevier, 2024)
Objective: Cerebral arteriovenous malformation during pregnancy is rare but lethal disease that usually present with new-onset seizures and headaches mimicking eclampsia. We report a rare case of cerebral arteriovenous malformation with abrupt seizures in the third trimester. Case Report: A 28-year-old primipara was brought to our emergency department at 32 6/7 weeks of gestation with new-onset acute seizures and hypertension. Owing to neurological deterioration, the patient underwent emergency cesarean delivery. However, 24 h after cesarean delivery and eclampsia treatment, the seizures worsened. Computed tomography and magnetic resonance imaging showed unruptured arteriovenous malformation of the right frontal lobe. Subsequently, intraarterial embolization was performed. The patient was discharged 5 days after surgery without neurological sequelae or obstetric complications. Conclusion: This case report highlights the differential diagnoses of sudden new-onset seizures in late pregnancy for obstetricians and emergency medicine physicians. Lethal cerebral diseases, apart from eclampsia, should be considered during pregnancy.